Effect of Thermal Radiation on Magneto-Convection of a Micropolar Nanoliquid towards a Non-Linear Stretching Surface with Convective Boundary - Jagan, K.; Sivasankaran, S.; Bhuvaneswari, M.; Rajan, S. (International Journal of Engineering and Technology, 2018)
The objective of this paper is to analyze the effect of thermal radiation on MHD mixed convection flow of a micropolar nanoliquid   towards a non-linear stretching surface with convective boundary condition. The governing equations are converted into non-linear    ordinary differential equations by using suitable similarity transformations. The homotopy analysis method is used for solving the non-linear ordinary differential equations. The temperature profiles increase due to increase in thermal radiation parameter. The microrotation   profile increases when boundary parameter is increased. Also, the skin friction coefficient and local Nusselt are plotted for various    parameters.